Magnetic chitosan grafted with polymerized thiourea for remazol brilliant blue R recovery: Effects of uptake conditions. Issue 7 (3rd July 2017) - Elwakeel, K. Z.; El-Bindary, A. A.; Ismail, A.; Morshidy, A. M.
ABSTRACT: Magnetic chitosan was prepared by co-precipitation with polymeric Schiff's base resulting from the reaction of thiourea with glutaraldehyde. This material has great potential as high-effective sorbent for Remazol Brilliant Blue R (RBBR): maximum sorption capacity reached 0.441 mmol g −1 at pH 1.6 and at 25°C. Kinetic plots, pH dependence, isotherm data, and influences of ionic strength were reported. The data from equilibrium sorption experiments are well fitted to the Langmuir isotherm and the pseudo-second-order sorption kinetics indicates that chemisorption controls the process. The distribution coefficient was calculated at different temperatures and the thermodynamic parameters have been calculated: the sorption reaction is endothermic, spontaneous, and increases the entropy of the system. Alkaline solution (0.5 M NaOH) was used for desorbing RBBR from loaded sorbent. The sorbent exhibited good regenerability over several repeated adsorption/desorption cycles. GRAPHICAL ABSTRACT: